Serenade for String trio, op. 8, published by Preston - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (London; United Kingdom; Preston, 2023)
Early edition of the Serenade for string trio in D major, op. 8, published by Preston from the plates of Broderip & Wilkinson.